THE SOCIAL IMPORTANCE OF DEVELOPING SANOGENIC THINKING IN A PERSON - Abdurahmanova Zuhra (Web of Journals Publishing, 2025)
This article presents the scientific views of scientists on the importance of thinking and thinking, the social psychological features of healthy thinking in the development of the individual.
Keywords: Personality, thought, thinking, sanogen thinking, motive, activity, behavior, activity, perfection, knowledge, skill.